PH-activated size reduction of large compound nanoparticles for in vivo nucleus-targeted drug delivery. (April 2016) - Fan, Yanbin; Li, Chunyan; Li, Fuyou; Chen, Daoyong
Abstract: Nucleus-targeted drug delivery is a promising strategy for anticancer therapy, but in vivo nucleus-targeted drug delivery has been challenging. Limited by the channel size of the nucleopore, vehicles that enter the nucleus via the nucleopore actively should be small and decorated with nuclear localization signal (NLS). However, the small vehicle size may promote leakage of vehicles into normal tissues, and the positively-charged NLS can lead to strong non-specific interactions in vivo . In the present study, we demonstrate an in vivo nucleus-targeted drug delivery using large compound nanoparticles with detachable PEG shell. The nanoparticles are composed of PEG-benzoic imine-oligo- l -lysine/iridium(III) metallodrug complex and formed in a kinetically-controlled fashion. Under physiological conditions (pH 7.4), the nanoparticles are large (ca. 150 nm) and protected by an inert PEG shell. When internalized into intracellular acidic endo/lysosomes of cancer cells, the nanoparticles dissociate into smaller ones ( ca. 40 nm) and the PEG chains detach due to the cleavage of the benzoic imine bond at low pH. The small nanoparticles, with exposure of the oligo- l -lysine after the detachment of the PEG shield, then translocate into the nucleus via the nucleopore due to the small size and nuclear localization ability of the oligo- l -lysine. Importantly, the small particles could significantly release the contained drug into the nucleus, leading to ca. 20-fold higher cytotoxicity compared to the native drug in vitro . Further in vivo application of the nucleus-targeting nano-system in a nude-mice model showed significant tumor inhibition and remarkable life-span elongation.